Efficacy of recombinant adenovirus expressing a fusion gene from GM-CSF and Epstein-Barr virus LMP2A in a mouse tumor model. Issue 10 (3rd October 2017) - Xue, Qingjie; Li, Xiuzhen; Yang, Chunqing; Ji, Bingyuan; Li, Yunqing; Yan, Yingchun; Yang, Xinxin; Wang, Chunmei; Chen, Ting
ABSTRACT: In this study, purified GM-CSF and LMP2A mRNAs were amplified by PCR. Then, the GM-CSF and LMP2A sequences were connected by the polypeptide linker (Gly4 Ser)3 using gene splicing by overlap extension. The constructed fusion gene GC2A was inserted into the adenovirus vector. Then the recombinant vector was introduced into HEK 293T cells by calcium phosphate transfection to package the adenovirus. The levels of antibodies against the GM-CSF and LMP2Afusion proteins were measured by ELISA, and the CTL activity of the mouse splenic lymphocytes was determined by lactate dehydrogenase (LDH) release assay. Immunotherapy of mouse tumor (EBV-positive epithelial tumor cell line (GT39)) tissues was performed, and their morphologies were assessed. Finally, the data of each group were analyzed using SPSS 11.5 statistical software. The recombinant adenovirus could replicate in HEK 293Tcells and induce humoral and cellular immune responses in the mice. The maximum dose resulted in an antibody titer of 18500 (184.5 ± 8.7 pg/ml). At an effector: target ratio of 40:1, maximum specific lysis was observed which was approximately three times that detected in the control immunized mice. The tumor inhibition rate was approximately 76% compared with the control groups, indicating the presence of significant differences among the groups. Tumor-infiltrating lymphocytes were detected by hematoxylin-eosin (HE) staining. The recombinant adenovirus induced humoral and cellular immune responses and inhibited tumor growth in mice. It provided a theoretical basis and candidate vaccine for further preclinical trials.